Сортове різноманіття щавнату (Rumex patientia L. × Rumex tianschаnicus Losinsk) та напрями його використання - Rakhmetov, D.B.; Rakhmetova, S.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The varietal diversification of shchavnat in dependence on the directions of its use is presented. Morphological and biological peculiarities, biochemical composition and productivity of different varieties of shchavnat are given.